Financing the Activities of Environmental Institutions in Poland and Ukraine to Preserve Ecosystems: Historical, Political and Managerial Aspects - Yakymchuk, Alina; Byrkovych, Victor; Valyukh, Liudmyla; Yakymchuk, Oleh (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
Preservation of the natural heritage for both Poland and Ukraine has been priority of sustainable development and public policies. Historically, both countries have a deep interest in the preservation of reserves, national nature parks and other categories of nature-protected fund and have had international cooperation for many years. However, the effectiveness of ecosystem conservation depends on the economic and financial instruments of public policy, which determined the relevance of this research topic. The basic principles of the state ecological policy of Ukraine for the period up to 2030, approved by the Law of Ukraine of February 28, 2019 № 2697-VIII, mention the possibility of development ecosystem services to ensure the sustainable development of society and the preservation of ecosystems. It is assumed that the biological diversity provided by ecosystem services should be preserved, assessed and restored accordingly. The State Forest Management Strategy of Ukraine until 2035 already provides for the monetization of ecosystem services in forestry, but only by reorganizing the system of calculation and use of environmental tax to allow the use of local and state environmental funds to pay for forest ecosystem services, measures maintaining the ecological sustainability of forests and preserving biodiversity in forests. For Ukraine, the positive experience of Poland in preserving ecosystems and monetizing the services and functions of ecosystems is important, which will be essential for the development of regulatory environmental policy of both countries. The main objectives of this work are to create a platform for cross-disciplinary dialogues that integrate different knowledge and research from diverse sectoral, geographical, historical, political, managerial and institutional perspectives and to develop an efficient system of preserving ecosystems, in particular to implement of international experience and to improve the socio-cultural development level of Ukraine.